(untitled) (Texas Journal of Medical Science, 2024)
This article explores the psycho-emotional conditions of young people with anaemia, exploring how the interplay between physical symptoms, cognitive difficulties and emotional distress may shape their mental health and social interactions. Understanding the psycho-emotional dimensions of anemia in young people is critical to providing comprehensive care and support tailored to their holistic well-being